Electroactive Organic Building Blocks for the Chemical Design of Functional Porous Frameworks (MOFs and COFs) in Electronics. Issue 48 (5th June 2020) - Souto, Manuel; Strutyński, Karol; Melle‐Franco, Manuel; Rocha, João
Abstract: Electroactive organic molecules have received a lot of attention in the field of electronics because of their fascinating electronic properties, easy functionalization and potential low cost towards their implementation in electronic devices. In recent years, electroactive organic molecules have also emerged as promising building blocks for the design and construction of crystalline porous frameworks such as metal–organic frameworks (MOFs) and covalent‐organic frameworks (COFs) for applications in electronics. Such porous materials present certain additional advantages such as, for example, an immense structural and functional versatility, combination of porosity with multiple electronic properties and the possibility of tuning their physical properties by post‐synthetic modifications. In this Review, we summarize the main electroactive organic building blocks used in the past few years for the design and construction of functional porous materials (MOFs and COFs) for electronics with special emphasis on their electronic structure and function relationships. The different building blocks have been classified based on the electronic nature and main function of the resulting porous frameworks. The design and synthesis of novel electroactive organic molecules is encouraged towards the construction of functional porous frameworks exhibiting new functions and applications in electronics. Abstract : Electroactive organic molecules have emerged as promising building blocks for the design of crystalline porous frameworks such as metal–organic frameworks (MOFs) and covalent organic frameworks (COFs) with numerous functions in electronics. This Review provides a library of electroactive organic building blocks recently employed in the construction of functional porous materials with applications in electronics.